On natural and artificial glocalization - Bagina, Elena (project baikal, 2021)
Glocalization is a point where globalization enters communities or phenomena of different styles, cultures and traditions, including the phenomena of fine arts and architecture. Artificial glocalization is a search and application of specific forms-signs, and creation of a set of characteristics symbolizing the local tradition. Natural glocalization occurs when the national culture is on the rise and is ready to accept any innovations without loss of identity, when it is not forms-signs that work, but forms-images, which are identified as national.